Technology-enhanced pre-instructional peer assessment: Exploring students’ perceptions in a Statistical Methods course - Yosep Dwi Kristanto (REID (Research and Evaluation in Education), 2018)
There has been strong interest among higher education institution in implementing technology-enhanced peer assessment as a tool for enhancing students’ learning. However, little is known on how to use the peer assessment system in pre-instructional activities. This study aims to explore how technology-enhanced peer assessment can be embedded into pre-instructional activities to enhance students’ learning. Therefore, the present study was an explorative descriptive study that used the qualitative approach to attain the research aim. This study used a questionnaire, students’ reflections, and interview in collecting student’s perceptions toward the interventions. The results suggest that the technology-enhanced pre-instructional peer assessment helps students to prepare the new content acquisition and become a source of students’ motivation in improving their learning performance for the following main body of the lesson. A set of practical suggestions is also proposed for designing and implementing technology-enhanced pre-instructional peer assessment.